2008
DOI: 10.1021/ma7021309
|View full text |Cite
|
Sign up to set email alerts
|

What Controls the Lamellar Orientation at the Surface of Polymer Films during Crystallization?

Abstract: The crystalline morphologies of poly(bisphenol A hexane ether) (BA-C6) films were investigated using atomic force microscopy (AFM). The glass transition temperatures (T g s) of the BA-C6 films on silicon wafers were determined using an ellipsometer, and the results indicated that the T g increased dramatically when the thickness of the films was smaller than about 30 nm. The lamellar orientation of the BA-C6 films with thicknesses of about 33 and 970 nm was studied at temperatures varying between the T g and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
139
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(146 citation statements)
references
References 57 publications
7
139
0
Order By: Relevance
“…Confinement of polymer systems can be generally classified into three categories according to their confined environments, and they are one, two and three dimensions, respectively. Confined crystallization of polymers has been found in a variety of systems, such as polymer ultrathin films [1][2][3][4][5], polymer blends [6][7][8][9][10], block copolymers [11][12][13][14], polymer droplets [15][16][17], self-assembled polymer nanostructures [18][19][20][21][22], polymers segregated inside nanoporous templates [23][24][25][26][27][28][29] and polymer nanocomposites [30][31][32][33]. In the past few years, the crystallization of polymers or polymer segments confined in ultrathin films (thickness <100 nm), miscible polymer blends and block copolymers has been widely studied for various systems.…”
Section: Introductionmentioning
confidence: 99%
“…Confinement of polymer systems can be generally classified into three categories according to their confined environments, and they are one, two and three dimensions, respectively. Confined crystallization of polymers has been found in a variety of systems, such as polymer ultrathin films [1][2][3][4][5], polymer blends [6][7][8][9][10], block copolymers [11][12][13][14], polymer droplets [15][16][17], self-assembled polymer nanostructures [18][19][20][21][22], polymers segregated inside nanoporous templates [23][24][25][26][27][28][29] and polymer nanocomposites [30][31][32][33]. In the past few years, the crystallization of polymers or polymer segments confined in ultrathin films (thickness <100 nm), miscible polymer blends and block copolymers has been widely studied for various systems.…”
Section: Introductionmentioning
confidence: 99%
“…At such a surface, the polymer crystals have two basic orientations: flat-on and edge-on orientations. Figure 1 is a schematic diagram showing these two orientations (Wang et al 2008). Wang et al (2008) found that edge-on and flat-on lamellae tend to develop at the surface of a polymer film at low and high temperatures, respectively.…”
Section: Semicrystalline Surfaces End-group Distribution At the Surfamentioning
confidence: 99%
“…Figure 1 is a schematic diagram showing these two orientations (Wang et al 2008). Wang et al (2008) found that edge-on and flat-on lamellae tend to develop at the surface of a polymer film at low and high temperatures, respectively. At temperatures above the glass transition temperature (T g ) of a polymer, edge-on lamellae are mostly observed at the surface.…”
Section: Semicrystalline Surfaces End-group Distribution At the Surfamentioning
confidence: 99%
See 2 more Smart Citations